Comparison of the safety and efficacy of intracervical Foleys catheter versus PGE2 gel for induction of labour at term - Patel, Prakruti P.; Bhabhor, Mittal V.; Jayswal, Pankti; Khatri, Saila A.; Brahmbhatt, Grishma P.; Patel, Megha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Before the induction of labour cervical ripening is needed for the success of induction to reduce the complication and diminish the rate of cesarean section and duration of labour. Various mechanical methods like Foleys catheter are effective but not much popular because of infection and pharmacological preparations which have more side effects, are used for cervical ripening. Therefore study has been conducted to compare the efficacy and safety of intra cervical Foleys catheter versus PGE2 gel for induction of labour at term. The aims and objectives of this study was to success of induction of labour depends on the cervical status at the time of induction. Methods: A prospective comparative study was conducted in the department of obstetrics and gynecology, L.G. hospital (AMCMET Medical college), Ahmedabad, during period of July 2019 to December 2019. 100 patients at term with a Bishop’s score with various indications for induction were randomly allocated to receive (50 patients) intra cervical Foleys catheter or PGE2 gel (50 patients). Post induction Bishop’s score was noted after 6 hours, 12 hours, 24 hours. Statistical methods used were Student t test and Chi square test to statistically compare the two groups. Differences with a p value of <0.005 was considered statistically significant with confidence limit of 95%. Results: The groups were comparable with respect to maternal age, gestational age, parity, indication of induction and initial bishops score. Both groups showed significant change in the Bishops score, 5.10±1.55 and 5.14±1.60 for Foleys catheter and PGE2 gel, respectively, p<0.001. Fetal outcome was noted in NICU admission and fetal death. No significant difference between two groups. Conclusions: This study shows that both Foleys catheter and PGE2 gel were equally effective in pre induction cervical ripening.